Grau de compactação, intervalo hídrico ótimo e permeabilidade ao ar de um latossolo vermelho distroférrico sob plantio direto - Betioli Junior, Edner (2012)
The objective of this study was to evaluate the physical quality of an Oxisol cultivated for 30 years under no-tillage (NT). For this purpose two experiments were conducted in an area of commercial fields located in Maringá, PR: in the first, soil samples with preserved and deformed structure were collected from de 0-0.10 m layer, for determination of bulk density (BD), the least limiting water range (LLWR) and the degree of compaction (DC). The samples with preserved structure were obtained at three sampling positions: on the lines (L); at the midpoint between two lines (E) and at an intermediate position (IP) between the L and E of corn plants. The water retention curve, the soil resistance curve and the BD were determined. The soil sample with deformed structure was used to obtain the compaction curve using the Proctor test. The maximum bulk density (Dmax) was obtained from the compaction curve and DC was determined by the ratio between the BD and Dmax. In the second experiment, the soil air permeability (Ka), the air-filled porosity (Єa) and pore continuity indices (K1 and N) were evaluated for the sampling positions related to the lines (L), to the midpoint between two lines (E) and to an intermediate position (IP) between the L and E. Forty samples were taken from each sampling position in a transect set perpendicularly to the planting lines of corn, in two depths (0-0.10 and 0.10-0.20 m). The Ka and the Єa were determined at the matric potentials of -2, -4, -6, -10, -30 e -50 kPa. The BD and the water content were determined too. The results showed that regardless of the critical limits of penetration resistance (PR) adopted, there was a reduction in the LLWR with increasing BD. The LLWR highest values were observed in the L sampling position and the use of the critical PR greater than 2.0 MPa resulted in a LLWR consistent with the physical quality of the soil for long time under NT. The Dmax was 1.52 kg dm-3 and the DC ranged from 64 to 87%, with the highest values obtained at positions E and IP. The different sampling positions were statistical differences in the Ka and pore continuity indices, with the higher values obtained in the L at the 0-0.10 m layer. However, these differences were not necessarily related to the observed differences in BD and Єa. The values of LLWR and DC obtained in this study indicate that the physical quality of this soil is not limiting for crop yields after 30 years under no tillage. The Ka has proved its ability to detect changes in the pore system and proved to be efficient in the evaluation of the soil physical quality of this study.